A new genus and species of Pseudothelphusidae (Decapoda: Brachyura) from Serra do Imeri, Guiana Shield highlands, Amazonas State, Brazil - Tavares, Marcos; Magalhães, Célio (Zootaxa, 2026)
A new genus and species of Kingsleyinae (Pseudothelphusidae) crab is described and illustrated from a tannin-rich stream in humid montane forest at 1,730 m elevation in Serra do Imeri, Guiana Shield highlands, northern Amazonia, is described and illustrated. Its phylogenetic position is inferred from mitochondrial COI sequences using Maximum Likelihood analysis, which supports the new taxon as the sister group of the kingsleyine genera Microthelphusa and Orthothelphusa. The new genus is compared with all other genera of Kingsleyinae. The paraphyly of Microthelphusa is briefly discussed, and M. marahuacaensis and M. guaiquinimaensis, both from the Venezuelan Amazon highlands, are transferred to the new genus. In addition, the highest elevation records for the 30 pseudothelphusid species known from Brazil are also summarized and briefly discussed.